Jurisdiction of courts under martial law - Medvedyk, Lev (Global Prosperity, 2023)
It has passed less than eight years since the introduction of emergency measures to overcome the terrorist threat in April 2014 to the start of a full-scale invasion on the 24th of February, 2022. Having received a smoldering military conflict with a much stronger neighbour, O. Turchynov, the acting President of Ukraine and at the same time the Chairman of the Verkhovna Rada of Ukraine, did not give a proper legal assessment of the actual circumstances. That is, calling the aggression of the Russian Federation a war, he did not fulfill the prescription of the Constitution of Ukraine to declare a state of war. Later, already in 2018, the President of Ukraine, P. Poroshenko, renamed this invasion to the Joint Forces Operation (JFO). On his initiative, the Constitution of Ukraine was amended in the area of justice. However, there was nothing included in the Fundamental Law that regulates the activities of the judiciary during a state of war or declaration of a martial law. Therefore, it was necessary to determine the basic principles of the judiciary during the war immediately after its beginning. Nevertheless, the most serious challenge demonstrated the decisiveness of the actions of the officials in an extremely difficult period. The algorithm of changes in the territorial jurisdiction of the court cases was introduced by coordinated actions of the judiciary; the successful implementation of ways of adapting the court’s jurisdiction by types of specialization for the period of the introduction of martial law in Ukraine was demonstrated. Cooperation between law enforcement agencies has been established in order to overcome the military aggression, both inside the country and in the international arena. All possible resources were mobilized at the same time, but the problems were solved gradually, according to the sequence of their arrival. Although the fuss could have been avoided by timely deciding on the priorities of domestic policy, having a long armed conflict on the eastern borders and the annexed peninsula in the south.